Analisis Pertumbuhan Dividen Dan Return On Equity (Roe) Terhadap Nilai Saham Yang Dinilai Dengan Metode Dividen Discount Model Pada Perusahaan Manufaktur Di BEI Periode 2022-2024 - Eka Sariningsih; Indah Lia Puspita; Jusuf Pujakesuma (Universitas Malahayati, 2025)
This study aims to analyze the effect of dividend growth and Return on Equity (ROE) on the stock value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024 using the Dividend Discount Model (DDM). The research objects are three companies: PT Unilever Indonesia Tbk (UNVR), PT Indofood CBP Sukses Makmur Tbk (ICBP), and PT Astra International Tbk (ASII). The study employs a quantitative approach with a causal research design, utilizing secondary data obtained from annual financial publications. The results indicate that the intrinsic values of the three companies’ stocks consistently exceeded their market prices throughout 2022–2024. UNVR, with its high ROE and large payout ratio, was able to sustain a dividend growth of 8.5%. ICBP exhibited significant dividend growth (10–11%), causing its intrinsic value to soar well above the market price. ASII maintained stable dividend growth (9%) with intrinsic values nearly four times higher than its market price. Overall, all three companies were found to be undervalued, suggesting that these stocks are attractive for long-term investment.